Comparison of Design Requirements for Non-Anchored and Anchored Sheet Piles as Retaining Wall in a Basement - Wardani, Mila K; Utami, Gati Sri; Syafiarti, Arintha I D; Lestari, Laras L (Journal of Earth and Marine Technology (JEMT), 2024)
The construction of a 9-meter deep basement on clay soil with a soft consistency necessitates the use of a sheet pile for soil retention. Selected due to the soft soil conditions and a high groundwater level at the site, the sheet pile effectively addresses these challenges. The design calculations for the sheet pile, based on the Terzaghi concept, incorporated both active and passive earth pressures determined using the Rankine method. Analysis revealed a lateral force of 19,624 t/m² at a depth of 9 meters. The resulting design specifies a 10-meter embedded concrete pile without anchors, requiring a total sheet pile length of 19 meters. The chosen sheet pile type is W-600 A-1000. Alternatively, with anchors, the design calls for a 4-meter depth using type W-325A-1000 concrete sheet pile, with one anchor installed at a depth of 3 meters. The anchor's tensile strength is 5.46 tonnes, resisting a force of 113.817 Tm with a diameter of 5 cm. Modelling analysis showed that unanchored sheet piles have a safety factor of 0.770 and exhibit lateral deformation of 0.00803 meters. Conversely, the addition of anchors enhances the safety factor to 1.146 and increases lateral deformation to 0.0195 meters, indicating that anchors significantly improve safety and reduce deformation.